Evaluación de la calidad de las aguas de los arroyos Ca'i Puente y Sati de Coronel Bogado con macro invertebrados como bioindicadores (Journal on studies and research of academic knowledge, 2015)
The study aimed to analyze the water quality of streams Ca'i Puente and Sat? using macro invertebrates as bioindicators. For this, it was applied the BMWP (Biological Monitoring Working Party) method which was adapted to Aguapey, stream it was also considered phicochemical parameters using the Simplified Water Quality Index (ISQA) and Resolution Nº 222/02 the Secretary of Environment of Paraguay. Saples were taken within March and July 2014 at four stations along the water courses. The results indicate that the abundance and species diversity were influenced by organic pollution, being the most abundant families the Chironomidae, Corixidae Glossiphoniidae. Analysis of the data determined that the waters of the streams were contaminated, with the stations number two and three were the most affected (highly polluted) due to effluents from domestic services and industrial activities of Coronel Bogado city with very high levels of total phosphorus and fecal coliforms.
Keywords: Water quality; invertebrates; Ca´i Puente; Satī